Vented Methane-air Explosion Overpressure Calculation—A simplified approach based on CFD - Li, J.; Hernandez, F.; Hao, Hong; Fang, Q.; Xiang, H.; Li, Zhan; Zhang, Xihong; Chen, L. (Elsevier, 2017)
This paper presents new correlations developed through numerical simulations to estimate peak overpressures for vented methane-air explosions in cylindrical enclosures. A series of experimental tests are carried out first and the results are used to validate the numerical models developed with the commercial CFD software FLACS. More than 350 simulations consisting of 16 enclosure scales, 12 vent area to enclosure roof area ratios, 8 gas equivalence ratios and 9 vent activation pressures are then carried out to develop the Vented Methane-air Explosion Overpressure Calculation (VMEOC) correlations. Parameters associated with burning velocity and turbulence generation, oscillatory combustion and flame instabilities in vented gas explosion are taken into account in the development of new correlations. Comparing to CFD simulations, the VMEOC correlations provide a faster way to estimate the peak overpressure of a vented explosion. Additionally, it is proved in this study that the VMEOC correlations are easier to use and more accurate than the equations given in the up-to-date industrial standard- NFPA-68 2013 edition.